Musical stimuli and performance of university students in a deep pool running protocol (Research, Society and Development, 2022)
This study aimed to analyze the effects of musical stimuli on university performance through heart rate and Rate of Perceived Exertion as a function of a running protocol in deep water. The sample consisted of 18 women aged between 18 and 30 years (23.44 ± 3.42) from Mossoró/RN. Participants were assessed on two separate days, one day with musical stimulation and the other without the stimulus. At the end of each stage reached within the test, the Heart Rate and Rate of Perceived Exertion of each participant were measured before the beginning of the next stage. To compare the performance variables with and without musical stimuli, the paired “t” test. p